2015
DOI: 10.1016/j.mimet.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Species identification within Acinetobacter calcoaceticus–baumannii complex using MALDI-TOF MS

Abstract: Acinetobacter baumannii, one of the more clinically relevant species in the Acinetobacter genus is well known to be multi-drug resistant and associated with bacteremia, urinary tract infection, pneumonia, wound infection and meningitis. However, it cannot be differentiated from closely related species such as A. calcoaceticus, A. pittii and A. nosocomialis by most phenotypic tests and can only be differentiated by specific, time consuming genotypic tests with very limited use in clinical microbiological labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…bronchioseptica and among Aeromonas species. It is worth noting that 16S rRNA sequencing was also inconclusive in many of these difficult-to-identify species groups, as previously described [12,56]. Further investigations are needed to determine which of these limitations are inherent to the technique and which can be overcome with broader spectra databases.…”
Section: Discussionmentioning
confidence: 87%
“…bronchioseptica and among Aeromonas species. It is worth noting that 16S rRNA sequencing was also inconclusive in many of these difficult-to-identify species groups, as previously described [12,56]. Further investigations are needed to determine which of these limitations are inherent to the technique and which can be overcome with broader spectra databases.…”
Section: Discussionmentioning
confidence: 87%
“…Species-level identification based on genetic methods (e.g., rpoB sequencing, rRNA intergenic spacer sequencing) has enabled differentiation of the A. baumannii complex species for research purposes. It has been demonstrated that MALDI-TOF MS can be utilized as an alternative method to reliably identify A. baumannii complex species (13,22,29,30). Using these methods, the prevalence of A. baumannii, A. nosocomialis, and A. pittii within the A. baumannii complex has been shown to be highly variable among clinical isolates depending on the epidemiological settings (31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…A log score of Ն1.7 denotes a probable species identification according to the manufacturer's recommendations, with a score of Ն2.0 denoting a positive identification; however, multiple publications have shown that lowering the threshold to 1.7 does not affect or minimally affects specificity (20,21). The MALDI Biotyper system can reliably determine the species of the A. baumannii complex organisms (13,22).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, many studies have explored alternative methods of microbial identification that are accurate, rapid, and cost-effective, such as MS and Raman spectroscopy (4, 10, 1218, 33, 34). Other methods, such as DNA sequencing and AST, have also been used to differentiate among strains of microorganisms, including A.…”
Section: Discussionmentioning
confidence: 99%
“…baumannii isolates at the species level (57, 33, 34), difficulties seem to arise with MS when it is applied for strain-level identification of A. baumannii isolates (4, 811).…”
Section: Discussionmentioning
confidence: 99%